Relationship between Work Safety Facilities, Work Environment, and Employee Welfare to Employee Performance in Fabrication Sector at PT. Trim Pandu Engineering - Qiftia, Silvi; Mardiani, Inna Nisawati (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This research aims to analyzed the relationship between work safety facilities, work environment, and employee walfare to employee performance in the fabrication sector at PT. Trim Pandu Engineering. Adequate work safety facilities are believed to able to create a safe work environment, thereby reducing the risk of work accidents and increasing productivity. Apart from that, employee well-being also plays an important role in maintaining job satisfaction and motivation which has impact on increasing work. The method used in this research is quantitative with a survey approach. Data collected throught cakes distributed to 82 employess of PT. Trim Pandu Engineering that work in the fabrication sector. The free variabels in this research are employee safety, work environment and employee welfare facilities, while the dependent variabel is employee performance. Data analysis was carried out using multiple linear regression tests to see the influence of the three independent variables on employee performance. The result of this research shows that employee safety, work environment, and employee welfare facilities are positively and significantly related to employee performance. Better work safety facilities have been proven to improve employee performance, as well as better employee welfare which has a significant impact on increasing productivitly and performance. This study suggest that company management should continue to improve work safety facilities and employee welfare to ensure optimal performance is achieved.